Higher doses of methotrexate associated with discontinuation of oral glucocorticoids after initiation of biological DMARDs: A retrospective observational study based on data from a Japanese multicenter registry study. Issue 4 (4th July 2021) - Suzuki, Mochihito; Kojima, Toshihisa; Takahashi, Nobunori; Asai, Shuji; Terabe, Kenya; Kaneko, Atsushi; Hirano, Yuji; Hanabayashi, Masahiro; Oguchi, Takeshi; Takagi, Hideki; Kanayama, Yasuhide; Yabe, Yuichiro; et al.
Abstract: Objective: Glucocorticoids are important drugs used to treat rheumatoid arthritis. We recommend glucocorticoid discontinuation as soon as possible given the associated side-effects, but many patients continue to take oral glucocorticoids long-term. The present study aimed to explore factors associated with glucocorticoid discontinuation at 52 weeks after initiating biological disease-modifying antirheumatic drugs (bDMARDs). Methods: Subjects were 564 patients from a Japanese multicenter registry who were administered glucocorticoids and methotrexate (MTX) followed by initiation of the first bDMARD. We examined the status of oral glucocorticoid use at 52 weeks after initiating the first bDMARD. Results: By 52 weeks after bDMARD initiation, 164 patients (29.1%) discontinued glucocorticoids. Multivariable analysis identified age, MTX dose, and glucocorticoid dose as factors independently associated with glucocorticoid discontinuation. After adjusting for baseline characteristics using propensity score matching, among patient groups administered MTX ≤ 8 mg/week and MTX > 8 mg/week, 105 pairs remained. A significantly higher rate of glucocorticoid discontinuation (41.0%) was noted for patients administered MTX > 8 mg/week. Conclusion: Our findings suggest that glucocorticoids may be discontinued after initiating bDMARDs. Moreover, higher MTX doses (>8 mg/week) at the time of bDMARD initiation were associated with glucocorticoid discontinuation among patients treated with bDMARDs.